Health anxiety during a global pandemic: a comparison of medical and non-medical students in Mashhad, Iran - Mahsa Nahidi; Mohammad Reza Fayyazi Bordbar; Hanieh Mohammadi; Negar Morovatdar; Maryam Emadzadeh; Hassan Mirshafiei (Frontiers in Psychiatry)
BackgroundThe COVID-19 pandemic has negatively impacted mental health worldwide, especially among healthcare professionals, including medical students, who were more exposed to pandemic-related stressors. However, health anxiety within this vulnerable group remains understudied.ObjectiveThis study aimed to assess and compare health anxiety and COVID-19 anxiety between medical and non-medical students during the COVID-19 pandemic and to identify factors associated with these forms of anxiety.MethodsThis cross-sectional study recruited Iranian medical and non-medical students studying in Mashhad via convenience sampling using messaging apps. Participants completed a self-reported questionnaire on demographic and social factors, along with the Health Anxiety Inventory (HAI) and the Corona Disease Anxiety Scale (CDAS), with higher scores reflecting greater symptom severity. Statistical analyses evaluated group differences, correlations between HAI and CDAS scores, and the influence of confounding variables.ResultsA total of 305 students participated, with 176 medical students (57.7%) and 129 non-medical students (42.3%). The majority (92.7%) reported mild COVID-19 anxiety, while 3.2% reported moderate and 0.98% reported severe COVID-19 anxiety. COVID-19 anxiety did not significantly differ between medical and non-medical students (P = 0.439). However, medical students reported significantly higher fear of illness consequences than non-medical students (P = 0.037), while no significant differences were found in susceptibility to disease (P = 0.299) or general health concern (P = 0.156). HAI and CDAS scores were significantly correlated (r = 0.30, P < 0.001). Based on logistic regression, Female gender (OR = 4.55, P = 0.002) was associated with susceptibility to health anxiety, while studying a non-medical major was associated with lower health anxiety (OR = 0.01, P < 0.001) and lower COVID-19 anxiety (OR = 0.05, P < 0.001).ConclusionMild COVID-19 anxiety was prevalent among both medical and non-medical students, with comparable levels of health anxiety across the groups. These findings suggest the need for targeted mental health support among students during pandemic conditions.